Pengaruh Literasi Keuangan Dan Pengelolaan Keuangan Terhadap Kinerja Keuangan Pada Umkm Kota Malang - Ida Ardila Syafitri Rumain; Ronny Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
Abstract This research was conducted at UMKM in Malang City. This study aims to examine the effect of financial literacy and financial management on financial performance of UMKM in Malang. The variables used are financial literacy and financial management as independent variables, while financial performance is the dependent variable. This type of research is explanatory research. The research method used in this research is a questionnaire. The tool used for data analysis in this study was to use a software application in the form of SPSS. The analysis used includes instrument testing, normality test, classical assumption test, multiple linear regression analysis, the coefficient of determination and hypothesis testing. The results showed that financial literacy and financial management had a significant effect on the financial performance of UMKM in Malang. The results of the study using the F test indicate that financial literacy and financial management simultaneously affect the financial performance of UMKM in Malang.Keywords: Financial Literacy, Financial Management and Financial Performance.